Integrating Whole Blood Transcriptomic Collection Procedures Into the Current Anti-Doping Testing System, Including Long-Term Storage and Re-Testing of Anti-Doping Samples - Lima, Giscard; Kolliari-Turner, Alexander; Malinsky, Fernanda Rossell; Guppy, Fergus M.; Martin, Renan Paulo; Wang, Guan; Voss, Sven Christian; Georgakopoulos, Costas; Borrione, Paolo; Pigozzi, Fabio; Pitsiladis, Yannis (Frontiers in Molecular Biosciences, 2021)
Introduction: Recombinant human erythropoietin administration studies involving “omics” approaches have demonstrated a gene-expression signature that could aid detection of blood doping. However, current anti-doping testing does not involve blood collection into tubes with RNA preservative. This study investigated if whole blood in long-term storage and whole blood leftover from standard haematological testing in short-term storage could be used for transcriptomic analysis despite lacking RNA preservation. Methods: Whole blood samples were collected from thirteen and fourteen male healthy individuals, for long-term and short-term storage experiments. Long-term storage: whole blood collected into Tempus™ tubes and K2EDTA tubes and subjected to long-term (i.e., −80°C) storage and RNA extracted. Short-term storage: whole blood collected into K2EDTA tubes and stored at 4°C for 6-48-hours, then incubated at room temperature for 1 and 2 hours prior to addition of RNA preservative. Results: The experiments provided RNA quality and purity for gene expression analysis. Principle Component Analysis of microarray and RNA-seq gene expression data. Long-term storage: When comparing gene expression between blood tubes with and without RNA preservation, 6% (4058 transcripts) were differentially expressed using microarray and 3.4% (658 transcripts) were differentially expressed using RNA-Seq. Short-term storage: Mean RNA integrity and yield was not significantly different at any of the time points. RNA-Seq analysis revealed a very small number (<100) of differentially expressed transcripts when comparing samples stored between 6 and 48-hours without RNA preservative. None of the genes previously described as blood doping biomarkers were differently expressed in both long- and short-term storage experiments. Conclusion: RNA quantity, purity and integrity was not significantly compromised from short- or long-term storage in blood storage tubes lacking RNA stabilisation, indicating that transcriptomic/omics analysis could be conducted using anti-doping samples collected or biobanked without RNA preservation.